3D in situ study of damage during a 'shear to tension' load path change in an aluminium alloy. (1st June 2022) - Kong, Xiang; Helfen, Lukas; Hurst, Mathias; Hänschke, Daniel; Missoum-Benziane, Djamel; Besson, Jacques; Baumbach, Tilo; Morgeneyer, Thilo F.
Graphical abstract: Abstract: A load path change (LPC) from shear to tension has been studied for a recrystallized 2198 T8 aluminium alloy sheet material by three-dimensional (3D) X-ray imaging combined with image correlation and interpreted by complementary 3D finite element (FE) simulations. A cross-shaped specimen was designed for the non-proportional loading and multiscale study. The effect of the LPC on the formability and related strain localisation, damage and failure was investigated and damage mechanisms could be clearly identified. The macroscopic tension stretch to fracture, measured by an optical extensometer during the shear to tension test, was reduced by about 20% compared to the proportional tension test. Damage, measured by in situ laminography imaging at μ m-scale resolution, has interestingly already been found under shear, and was quantified as surface void fraction during the LPC. Strain was measured inside the material and at the mesoscale by 2D digital image correlation (DIC) on projected volume data, using the (natural) intermetallic particle contrast present in the 3D laminographic data. An accumulated equivalent strain definition, suited for the description of non-proportional loading, has been applied to the DIC data and FE simulations, indicating good agreement between both. On the microscopic scale, damage was seen to nucleate under shear load in the form of flat cracks, of similar width as the grain size, and in the form of cracks inside intermetallic particles. This damage subsequently grew and coalesced during tensile loading which in turn led to final fracture.